Implementasi Model Pembelajaran Team Game Tournament untuk Meningkatkan Hasil Belajar Bahasa Inggris - Mohammad Umar (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2021)
The problem of this research is whether the Team Game Tournament Learning Model (TGT) can improve the English learning achievement of calss XI IPS-3 students of MAN 1 Kudus in the even semester of the academic year 2018/2019. The purpose of this study is to find out that the implementation of the Team Game Tournament Learning Model (TGT) can improve English learning achievement of class XI IPS-3 students of MAN 1 Kudus in the even semester of the academic year 2018/2019. The results of the study showed that there is an improvement of the English learning achievement of class XI IPS-3 students. The improvement was indicated by: (1) the average learning achievement in cycle I is 7.14; cycle II 7.44; and 8.84 in cycle III; (2) the learning completion in cycle I is 47.22% of all students and the incompleted students is 52.78%; the completed students in cycle II is 72.22% and the incompleted students is 27.78%; in cycle III, the completed students in cycle III is 100%; (3) the classical learning completion in cycle I is 47.22%, in cycle II reaches 72.22; cycle III reaches 100%.